Prospek Industri Meubel Terhadap Pendapatan Keluarga Pengrajin Di Kelurahan Malewang Kecamatan Polombangkeng Utara Kabupaten Takalar - Hasmiati, Hasmiati (UNIVERSITAS NEGERI MAKASSAR, 2018)
Research aims to understand : 1) What factors that supports and hindered the development of industry furniture 2) How distribution marketing industry furniture 3) Is there influence significant industry furniture. The variables that will be investigated in this study , which is the amount of raw materials , amount of capital , the amount of labor , technology to be used , amount of produce , the distribution of marketing , level of income , a population of which is 25 Entrepreneurs , data collection through technique observation , interview , documentation .Then in analysis using descriptive statistics and inferential . The research results show 1). Factors that support in developing industry furniture there are locations , strategic , raw materials available , labor skilled , advanced technology .Factors that impede in developing industry furniture and: limited capital , transportation used still using a rent 2) Distribution markets for produce furniture through orders directly to the locations of industry , through shops nearest , and distribution of to various regions that is makassar , gowa , sinjai , bantaaeng , bulukumba , bone 3) Capital and produce having influence a significant impact on income the bigger capital the higher income results furniture, including with the volume of production, the bigger the volume of production the bigger also the income . The development of industry furniture in malewang village polombangkeng utara district and takalar regency have qualified when viewed from the perspective of the results of prosuksi and the location of marketing